Children and the Imago Dei: A Reformed Proposal Regarding the Spiritual Openness of the Child - Barfield, Robin (Christian education journal, 2020)
The spiritual openness of the child has been explained by their being at their existential limits and more open to mystery. This results in a non-directive approach to ministry, affirming every response and emphasizing the creative nature of the ṣeleʿm. This article proposes that a child is a "wiggly mirror," able to reflect divine glory or created idols which better enables us to understand the process of ministry to children and to construct a more robust pedagogy.